Development of Hertovid (History Vertical Short Video) Based on YouTube Short on the Sendang Duwur Tomb Site Material for Students of SMAN 1 Paciran Lamongan - Nabih Mufarrih; Najib Jauhari (Universitas Hamzanwadi, 2026)
The media becomes something important in the learning process. Technological development that has been used massively has an impact on efficiency in various aspects of life, should be utilized in the development of learning media. The purpose of this study is to develop a learning media called Hertovid (History Vertical Short Video) based on YouTube Shorts and evaluate its validity, feasibility of learning media, and effectiveness. Hertovid containing historical content of the Sendang Duwur Tomb Site. The development of Hertovid in this study uses the Research and Development (R&D) method, following Sugiyono's model. At the product design validation carried out by material expert validators, obtaining 94,5%, and the media expert obtained 91,1%. The subjects used in the product initial trial and the product usage trial were 31 students from class X-E2 SMAN 1 Paciran. The percentage of 85,73% obtained from the initial trial result and 86,45% from the usage trial result. From this study, data were obtained that Hertovid is a historical learning media that is very feasible to use in learning and effective in improving students' understanding of the Sendang Duwur Tomb Site content.